Oxidative stress, fibrosis, and early afterdepolarization-mediated cardiac arrhythmias - Karagueuzian, Hrayr; Nguyen, Thao P.; Qu, Zhilin; Weiss, James N. (Frontiers in Physiology, 2013)
Animal and clinical studies have demonstrated that oxidative stress, a common pathophysiological factor in cardiac disease, reduces repolarization reserve by enhancing the L-type calcium current, the late Na, and the Na-Ca exchanger, promoting early afterdepolarizations (EADs) that can initiate ventricular tachycardia and ventricular fibrillation (VT/VF) in structurally remodeled hearts. Increased ventricular fibrosis plays a key facilitatory role in allowing oxidative-stress induced EADs to manifest as triggered activity and VT/VF, since normal non-fibrotic hearts are resistant to arrhythmias when challenged with similar or higher levels of oxidative stress. The findings imply that antifibrotic therapy, in addition to therapies designed to suppress EAD formation at the cellular level, may be synergistic in reducing the risk of sudden cardiac death.